The impact of pecuniary costs on commuting flows - David McArthur; Gisle Kleppe; Inge Thorsen; Jan Uboe (European Regional Science Association (ERSA), 2010)
In many cases fjords cause disconnections in the road network, calling for the service of ferries. The construction of bridges or subsea tunnels may, however, substitute the ferries, often financed by toll charges. In this paper we use data on commuting flows from a Norwegian region with a high number of ferry connections and/or tunnels and bridges. Based on a doubly-constrained gravity-based model specification we focus on how commuting flows respond to varying toll charges and ferry prices. Estimation results are used to predict how the generation and distribution of commuting flows is affected when ferry connections are substituted by bridges and tunnels. We also estimate the willingness to pay for a new road connection, and predict how commuting flows respond to alternative pricing policies for the new road link.
Keywords: R41; R48; R12; 330; Commuting; Pecuniary costs; Gravity model; Toll charges; Investment financing